A comparison among bio-derived acids as selective eco-friendly leaching agents for cobalt: the case study of hard-metal waste enhancement - Oumarou Amadou, Amadou; Cera, Martina; Trudu, Stefano; Piredda, Martina; Cara, Stefano; De Gaudenzi, Gian Pietro; Matharu, Avtar Singh; Marchiò, Luciano; Tegoni, Matteo; Muntoni, Aldo; De Gioannis, Giorgia; Serpe, Angela (Frontiers in Environmental Chemistry, 2023)
Peculiar chemical, mechanical and magnetic properties make cobalt a key metal for a variety of “hot” applications like cathode production of Li-ion batteries. Cobalt is also the preferred metallic binder for tungsten carbide tools manufacturing. The recent increasing criticality of cobalt and tungsten is driving the interest of manufacturers and researchers towards high-rate recycling of Hard Metals (HMs) waste for limiting the demand of raw materials. A simple and environmentally friendly hydrometallurgical route for Co selective dissolution from HM wastes was developed by using weak, bio-derived and biodegradable organic acids (OAs). In this study OAs, namely acetic (HAc), citric (H3Cit), maleic (H2Mal), lactic (HLac), succinic (H2Suc), lactobionic (HLB), and itaconic (H2It) acids, were selected for their pKa1 values spanning from 1.8 to 4.7 and systematically tested as selective cobalt leaching agents from WC-Co-based wastes in water, isolating the formed complexes at the solid state. Thereby, all of them seemed to be efficient in selective Co-leaching, achieving almost quantitative Co dissolution from HM by-products still at low concentration level and room conditions in a short time, leaving the residual WC unreacted and ready to be re-employed for industrial purposes. Nevertheless, two main categories of organic acids were distinguished depending on their oxidizing/complexing behavior: Class 1 OAs, where the metal oxidation is carried out by H+; Class 2 OAs where oxidation is played by an external oxidant like O2. A combined experimental/theoretical investigation is here described to show the reasons behind this peculiar behavior and laid the foundation for a wider discussion on the leaching capabilities of OAs towards elemental metals. Due to the demonstrated effectiveness, low cost, eco-friendliness and large availability through biotechnological fermentative processes, particular attention is here devoted to the use of HLac in hydrometallurgy as an example of Class 2 OA. WC-Co materials recovered by HLac mild hydrometallurgy demonstrated a metallurgical quality suitable for re-employment in the HM manufacturing process.